1ª série do ensino médio em Pato Branco: motivações dos jovens para o abandono - Rodrigues, Rodinéia Rekssua (2021)
To talk about School Abandonment and Dropout is not an easy task, particularly because this topic leads us to analyze School Failure, too. Considering that many young people abandon school in the first years of high school, our research aimed to understand the motivations leading them to abandon it in the freshman year, which often ends up in dropout. Given the fact that young people are the main subject of the issue, we discussed who they are, how they are understood throughout the years, and in the present. It is qualitative research that dialogues in methodological terms with historical materialism, and with a sociocultural perspective. In addition to a literature review, we used documents for data collection, and on-line questionnaires via Google Forms and semi-structured interviews, both with young people and representatives of the pedagogical boards of schools studied. To delimit the number of subjects participating in the research, a timeframe from 2017 to 2020 was established, in three public schools of Pato Branco city presenting the higher rate of school abandonment in freshman year. The thesis is composed of three main chapters. The first one brings about the theoretical contributions on School Failure in Brazil, the second one addresses today’s youths in the schools, and the third one addresses the motivations leading them to abandon school. After students and members of the pedagogical board turned in their questionnaires and with the participation of students in our semi-structured interviews, we realized the extent to which these students’ reasons to abandon school are related to factors beyond school organization, accounting them for their decision-making. Regarding young people, we could see their hope towards schools demands a macrosocial understanding of what it means to be young today. In their contribution, it was possible to see that the decision for school abandonment permeates sociocultural and economic questions. They go beyond the trivial understanding that young people are not interested in school training. It was also seen that they present a life project, even when the decision they make does not favor their continuation in school. Often it happens due to the situations they experience. Thus, what young people expect from school demands an macrosocial understanding of what it means to be young today.